The Determinants of Corporate Cash Holdings- An Empirical study from UK Firms - GUO, YI (2013)
Cash holding is most important financial decision in the company management strategy. In this dissertation, the determinants of corporate cash holdings in UK non-financial publicly traded firms over the period from 2003 to 2012 are investigated. Our study finds that growth opportunities and cash flow and cash flow variability are positively associated with the level of corporate cash holdings, while firm size, leverage, net working capital, bank debt and dividend payment have negative impact on corporate cash holdings. By investigating the influence of financial constraints, we find firms with financial constraints expect to hold a large amount of cash. The results suggest that the determinants of corporate cash holdings in UK firms are well explained by trade-off theory and pecking order theory.